Numerical and experimental study of thermal fluid flow and keyhole dynamic in laser welding of aluminum alloy assisted by electromagnetic field. (January 2023) - Tan, Caiwang; Liu, Yuhang; Xu, Bingxiao; Wang, Houqin; Liu, Fuyun; Gong, Xiangtao; Zeng, Zhi; Chen, Bo; Song, Xiaoguo
Highlights: A steady electromagnetic field is designed to suppress defect of laser welded joint. Develop a 3D model to analyze thermal fluid flow in magnetic-assisted laser welding. Influencing mechanism of magnetic field on stabilizing keyhole is revealed. The numerical model is validated by the experimental analysis. Abstract: A steady electromagnetic field with high magnetic flux density was designed to improve weld appearance and suppress porosity defect of aluminum alloy laser welded joint. A comprehensive numerical model considering the multiple reflection of laser beam, the magnetohydrodynamics (MHD), and the vapor shear stress on free surface of keyhole was established to reveal the effect of electromagnetic field on thermal fluid flow and keyhole dynamic. A sufficient Lorentz force (∼1.255 × 10 6  N/m 3 ) is induced when magnetic flux density reaches to 500 mT. The fluids flow downward, forward, and upward in the upper, middle, and lower region are inhibited by the Lorentz force, respectively. Therefore, less heat exists in the bottom and more heat accumulates in the middle edge of the weld pool, leading to the smaller weld depth, larger length at half depth, and disappeared necking when an electromagnetic field is used. Moreover, the impact of vortex on the rear keyhole wall is weakened by the Lorentz force, which decreases the oscillation and breakup of keyhole. This work can help improve the understanding concerning influence of the electromagnetic field on thermal fluid flow behavior in laser welding and provide guidelines for the suppression of porosity and splash defects.